Integrative Korean Medicine for Pain and Functional Recovery in Lumbar Transverse Process Fractures: A Case Report and Literature Review - Ji-Sun Kim; Gyu-Bin Lee; Hong-Wook Choi; Do-Young Kim; Dong-Jin Kim; Dong-Ju Yoon; Ye-Rim Yun; Ji-Sung Yeum; Ik-Jun Cho (Journal of Acupuncture Research)
The transverse processes function as essential attachment points for the muscles and ligaments surrounding the spine, and transverse process fractures (TPF) are commonly observed in trauma patients, such as those involved in traffic accidents. However, studies investigating the effectiveness of integrated Korean medicine (iKM) treatments for lumbar TPF have been limited. The present study aims to report a case of a traffic accident-induced lumbar TPF treated with iKM, which indicated significant improvement in pain and function. The patient was diagnosed with left TPFs at the L3 and L4 vertebral levels via radiological examination and underwent iKM treatments. After two weeks of iKM hospitalization, the numerical rating scale scores decreased from 5 to 3, the Oswestry Disability Index scores decreased from 53.33 to 35.56, and the EuroQoL-5 dimension scores increased from 0.675 to 0.771. In conclusion, our findings suggest that iKM treatments may be effective for patients with lumbar TPF in terms of pain and functional management.